RESEARCH ON THE MUSIC EDUCATIONAL PERSPECTIVES IN THE CONDITIONS OF DIGITAL TRANSFORMATION - A. Islam (Trakia Journal of Sciences)
Information technologies received increased attention in education over the past decade. Computers have become an almost indispensable aid of digital technology in teaching, but their purpose is not to replace the teacher but to complement his teaching. This paper explores how these technologies can be effectively incorporated into music pedagogy to support students' musical development, cognitive motivation, and information literacy. Through a qualitative meta-analysis of peer-reviewed papers, studies, andrelated reports, this research underscores the necessity of digital resources in contemporary education. The analysis reveals that digital technologies not only align with the realities of students' everyday lives but also stimulate curiosity, boost engagement, and lead to more effective learning outcomes. The study advocates for the thoughtful incorporation of these technologies into music education curricula, ensuring that they complement rather than replace traditional teaching methods. The primary contribution of this research is the demonstration that digital technologies, when effectively integrated, create meaningful and pedagogically sound experiences in music education and play a critical role in enhancing and promoting music learning, empowering students to take control of their educational journey. This approach fosters innovation, creativity, and active participation, which are essential for the development of 21st-century learners.